Impact of maternal iron and zinc intake on low birth weight risk: a nested case—control study - Liping Yang; Zifu Wang; Lei Cao; Yuqing Li; Jingyan Wang; Shuyu Ding; Baohong Mao (PeerJ)
Background The association between maternal iron/zinc intake and the risk of low birth weight (LBW) in infants is still unclear. This study aimed to investigate the effects of iron and zinc daily intake preconception and during pregnancy on the risk of delivering LBW babies and to assess whether there is an interaction between iron and zinc intake on the risk of LBW. Methods A nested case–control study was performed, including 565 cases and 7,510 controls in Lanzhou City, China. Eligible participants were interviewed about their diets and characteristics during pregnancy. Unconditional logistic regression was used to determine the association between dietary iron/zinc intake and the risk of LBW and its clinical subtypes. Multivariate-adjusted restricted cubic spline (RCS) models were applied to explore the nonlinear association between dietary iron/zinc intake levels and the risk of LBW. Results Lower intake of iron/zinc preconception and during pregnancy was associated with a higher risk of LBW and some subtypes, and there was a nonlinear trend between iron/zinc intake and the occurrence risk of LBW (PNonlinear < 0.05). Moreover, the synergistic effects of low iron and low zinc intake on the risk of LBW were found. Conclusion Efforts to promote iron and zinc intake preconception and during pregnancy need to be strengthened to reduce the local incidence of LBW.